If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 8) + 2 = 38 Reorder the terms: 9(8 + x) + 2 = 38 (8 * 9 + x * 9) + 2 = 38 (72 + 9x) + 2 = 38 Reorder the terms: 72 + 2 + 9x = 38 Combine like terms: 72 + 2 = 74 74 + 9x = 38 Solving 74 + 9x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-74' to each side of the equation. 74 + -74 + 9x = 38 + -74 Combine like terms: 74 + -74 = 0 0 + 9x = 38 + -74 9x = 38 + -74 Combine like terms: 38 + -74 = -36 9x = -36 Divide each side by '9'. x = -4 Simplifying x = -4
| 6(r-6)=-66 | | 8x(2n+3x)=10 | | 21n^2+14n+7=6n+11 | | -(4-5z)-2(-3z+4)-3z=-2(6-4z-8(1-z)) | | 5(3-5n)=65 | | 21n^2+8-4=6n+11 | | 5+6-3x=-4 | | 5a-10b=45 | | 4x+89=6x+109 | | 21n^2+8-4= | | 15-2y=15+3y | | X^2-2ax=6ab-3bx | | 5(s-1)=94-2(s-4) | | 4x-5+6=45 | | 20x=280 | | x^3-31x-30=0 | | 3a+b=54 | | -3(2y-4)-6= | | (5p-3p)=2p+9 | | 16x-13=7x+32 | | 2z^2+19-10=0 | | 4.9=4t+(-7t) | | -24=-4y-8 | | 18x-13=6x+47 | | 2x+(y^2)+2=0 | | -9x-4y=-1 | | -14x-4=-13x+6 | | 2w+2(2w+1)=36 | | 1.6y+12y=0 | | 18x+12=12x+6 | | 1.2x-9=-11 | | -15x-3=-10x-18 |